Nanoelectromechanical-Switch-Based Binary Content-Addressable Memory (NEMBCAM) - Jae Seong Lee; Woo Young Choi (IEEE Access, 2021)
This paper proposes a novel nanoelectromechanical-switch-based binary content-addressable memory (NEMBCAM) for the first time. A nanoelectromechanical (NEM) memory switch serves as both a nonvolatile memory and a switchable current path in an NEMBCAM unit cell. Owing to monolithic three-dimensional integration, NEMBCAM achieves a smaller unit cell area in comparison with conventional complementary metal–oxide–semiconductor-only binary content-addressable memory. Small unit cell area results in reduced match line (ML) capacitance, which lowers search energy consumption. Furthermore, a shorter search delay is achieved owing to the near-perfect on/off characteristic of the NEM memory switch.